Identity and Otherness in Vento ferido by Carlos Casares - Piñeiro Pais, Laura (Madrygal. Revista de Estudios Gallegos, 2015)
Vento ferido of Carlos Casares is ascribed to the canon of “Nova Narrativa Galega”. However, although literary criticism often links Vento ferido with this group, we can see the influence of some Galician authors from the earlier tradition in the stories that make up this work. This article aims to investigate if Castelao and Dieste have influenced Carlos Casares’ search for his own identity focusing on two works: Cousas and Dos arquivos do trasno.